Anti-aging anticorrosive paint and preparation method thereof

The preparation of anti-aging anti-corrosion coatings by reacting layered magnesium aluminum hydroxide with other materials has solved the problem of degradation in the performance of existing coatings and achieved good corrosion resistance, flame retardant, antibacterial and self-repairing properties.

CN119286370AInactive Publication Date: 2025-01-10WUHAN XINYUKANG ENVIRONMENTAL PROTECTION NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411364327.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anticorrosion coatings are prone to cracks, perforations and delamination during use, resulting in degradation of performance and lack of effective flame retardant, antibacterial and self-repairing properties.

Method used

Anti-aging anti-corrosion coatings are prepared by reacting layered magnesium aluminum hydroxide with chloropropyltrimethoxysilane, N-(2-(N,N-dimethylamino)ethyl)maleimide and other materials, and through Components such as 1H-pyrrole-2,5-diformaldehyde dioxime and isophorone diisocyanate are introduced to form a prepolymer solution and mix it with aluminum trichloride and polyetheramine to form a coating with a layered structure.

Benefits of technology

It improves the corrosion resistance, flame retardant, antibacterial and self-healing properties of the paint, extends the diffusion path of oxygen and water molecules, reduces the thermal decomposition rate, and enhances the anticorrosion and tensile strength of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065818710000031
    Figure BDA0005065818710000031
  • Figure BDA0005065818710000151
    Figure BDA0005065818710000151
  • Figure BDA0005065818710000161
    Figure BDA0005065818710000161
Patent Text Reader

Abstract

The invention discloses an anti-aging anticorrosive coating and a preparation method thereof, and relates to the field of coatings. When the anti-aging and anti-corrosion coating is prepared, layered magnesium aluminum hydroxide and 3, 5-di-tert-butyl-4-hydroxybenzoic acid are subjected to a reaction, and anti-aging layered magnesium aluminum hydroxide is prepared; the preparation method comprises the following steps: reacting the anti-aging layered magnesium aluminum hydroxide with chloropropyltrimethoxysilane and N-(2-(N, N-dimethylamino) ethyl) maleimide to prepare a modified layered magnesium aluminum hydroxide; the preparation method comprises the following steps: carrying out a reaction on polytetrahydrofuran, 1H-pyrrole-2, 5-diformaldehyde dioxime, n-dodecyl phosphonic acid, isophorone diisocyanate and diphenylmethane diisocyanate to prepare a prepolymer solution; and uniformly mixing the prepolymer solution with the modified layered magnesium-aluminum hydroxide and aluminum trichloride, and then adding polyether amine to prepare the anti-aging and anti-corrosion coating. The anti-aging anticorrosive paint prepared by the invention has good corrosion resistance, flame retardance, tensile strength and self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, in particular to an anti-aging and anti-corrosion coating and a preparation method thereof. Background Art

[0002] Metals exposed to the outside are susceptible to various corrosion damages. The main anti-corrosion technologies currently used include alloying treatment, medium treatment, electrochemical protection, adding corrosion inhibitors, surface coatings, etc. Paint anti-corrosion mainly inhibits chemical and electrochemical corrosion by blocking the contact between the substrate and the corrosive medium, and can give the substrate special surface functions. The coating anti-corrosion technology is widely used, easy to construct, adaptable to a variety of application scenarios, and can be used together with other protective measures. It is widely used in many fields such as ocean, energy, construction, transportation, aerospace and military equipment.

[0003] Anticorrosion coating is the most common and widely used method for metal corrosion prevention. However, the material will inevitably suffer a series of damages during use, including cracks, perforations and delamination, which will lead to performance degradation and even cause safety problems. The anti-aging anticorrosion coating prepared by the present invention has good anticorrosion performance, flame retardant performance, tensile strength and self-repairing performance, and has a good market prospect. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an anti-aging and anti-corrosion coating to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an anti-aging and anti-corrosion coating. The anti-aging and anti-corrosion coating is prepared by reacting layered magnesium aluminum hydroxide with 3,5-di-tert-butyl-4-hydroxybenzoic acid to obtain the anti-aging layered magnesium aluminum hydroxide; reacting the anti-aging layered magnesium aluminum hydroxide with chloropropyltrimethoxysilane and N-(2-(N,N-dimethylamino)ethyl)maleimide to obtain a modified layered magnesium aluminum hydroxide; reacting polytetrahydrofuran, 1H-pyrrole-2,5-diformaldehyde dioxime, n-dodecylphosphonic acid, isophorone diisocyanate and diphenylmethane diisocyanate to obtain a prepolymer solution; and mixing the prepolymer solution with the modified layered magnesium aluminum hydroxide and aluminum chloride and then adding polyetheramine to mix the mixture to obtain the anti-aging and anti-corrosion coating.

[0007] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0008] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution by volume concentration are mixed in a mass ratio of 1: (1.3-1.5): (1.4-1.6): (75-85), stirred at room temperature at 400-600 r / min for 5-7 hours, evaporated to remove the solvent at 80-90° C., dissolved the solid product in deionized water at 55-65° C., cooled to room temperature, filtered, and the dissolution-cooling-filtration operation is repeated 2-4 times, and the filter residue is vacuum dried at 75-85° C. for 8-12 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0009] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1: (0.4-0.6): (5-15) to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (8-12) to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 600-800 r / min. After the addition is completed, the mixture is allowed to stand for 10-14 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 3-5 times, and vacuum dried at 75-85° C. for 8-12 hours to obtain a layered magnesium aluminum precipitate. Hydroxide; mixing layered magnesium aluminum hydroxide and deionized water in a mass ratio of 1: (4-6), ultrasonically treating for 25-35 minutes to obtain layered magnesium aluminum hydroxide slurry; mixing 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide and deionized water in a mass ratio of 1: (0.3-0.5): (20-30), adding to the layered magnesium aluminum hydroxide slurry, sealing, stirring at 400-600 r / min at room temperature for 22-26 hours, filtering, washing the filter residue with deionized water for 3-5 times, and vacuum drying at 75-85° C. for 8-12 hours to obtain anti-aging layered magnesium aluminum hydroxide;

[0010] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1: (8-12): (30-40), reflux at a constant temperature of 105-115° C. for 22-26 hours under a nitrogen atmosphere, cool to room temperature, filter, wash the filter residue with anhydrous toluene for 3-5 times, and vacuum dry at 85-95° C. for 4-6 hours to obtain a pre-modified layered magnesium aluminum hydroxide;

[0011] (4) mixing the pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol in a mass ratio of 1:(1.2-1.4):(8-12), stirring at 75-85° C. and 600-800 r / min for 22-26 h, filtering, washing the filter residue with anhydrous toluene for 3-5 times, and vacuum drying at 85-95° C. for 4-6 h to obtain a modified layered magnesium aluminum hydroxide;

[0012] (5) Polytetrahydrofuran, 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and n-dodecylphosphonic acid are mixed to obtain a mixed solution, and diisobutyltin dilaurate in an amount of 0.2 to 0.4 times the mass of polytetrahydrofuran and N,N-dimethylformamide in an amount of 20 to 30 times the mass of polytetrahydrofuran are added; isophorone diisocyanate and diphenylmethane diisocyanate are mixed in proportion and added, and stirred at 65 to 75° C. and 200 to 400 r / min for 2 to 4 hours to obtain a prepolymer solution;

[0013] (6) Modified layered magnesium aluminum hydroxide, prepolymer solution, and aluminum chloride are mixed in a mass ratio of 1:

[0014] (30-40): (0.7-0.9) are mixed, polyether amine with a molar number of 1.6-2 times of isophorone isocyanate and N,N-dimethylformamide are mixed in a mass ratio of 1: (18-22) and then added, and stirred at 400-600r / min for 8-12min at 45-55°C to obtain an anti-aging and anti-corrosion coating.

[0015] As an optimization, the 1H-pyrrole-2,5-dicarboxaldehyde dioxime reaction process described in step (1) is as follows:

[0016]

[0017] As an optimization, the polytetrahydrofuran described in step (5) is polytetrahydrofuran with an average molecular weight of 1000.

[0018] As an optimization, the molar ratio of polytetrahydrofuran, 1H-pyrrole-2,5-dicarbaldehyde dioxime, n-dodecylphosphonic acid, isophorone diisocyanate, and diphenylmethane diisocyanate in the prepolymer solution of step (5) is 1:0.2:0.2:2.8:1.2.

[0019] As an optimization, the polyetheramine described in step (7) is T403 polyetheramine, which was purchased from Shandong Mingsheng Chemical Technology Co., Ltd.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] When preparing the anti-aging and anti-corrosion coating, the present invention comprises the following steps: reacting layered magnesium aluminum hydroxide with 3,5-di-tert-butyl-4-hydroxybenzoic acid to obtain the anti-aging layered magnesium aluminum hydroxide; reacting the anti-aging layered magnesium aluminum hydroxide with chloropropyltrimethoxysilane and N-(2-(N,N-dimethylamino)ethyl)maleimide to obtain the modified layered magnesium aluminum hydroxide; reacting polytetrahydrofuran, 1H-pyrrole-2,5-diformaldehyde dioxime, n-dodecylphosphonic acid, isophorone diisocyanate and diphenylmethane diisocyanate to obtain the prepolymer solution; reacting the prepolymer solution with the modified layered magnesium aluminum hydroxide and aluminum chloride, and then adding polyetheramine to obtain the anti-aging and anti-corrosion coating.

[0022] Firstly, n-dodecylphosphonic acid is introduced into the main chain of the coating. When heated and burned, phosphoric acid will undergo dehydration polymerization to regenerate polymetaphosphoric acid. Polymetaphosphoric acid can quickly catalyze the dehydration and carbonization of polyurea materials to generate a dense protective carbon layer, isolate oxygen and reduce the thermal decomposition rate of the material, so that the maximum mass loss rate of polyurea is gradually reduced, while reducing the heat generated by the decomposition of the coating, thereby improving the flame retardant properties of the anti-aging and anti-corrosion coating; 1H-pyrrole-2,5-dicarboxaldehyde dioxime is introduced into the main chain of the coating so that the main chain contains an oxime-amino bond. The presence of the imine bond can complex metal ions and improve the corrosion resistance of the coating. The pyrrole structure can undergo a thermally reversible cross-linking reaction with the maleimide structure on the modified layered magnesium aluminum hydroxide, thereby improving the tensile strength of the anti-aging and anti-corrosion coating. In addition, according to the thermally reversible cross-linking reaction, the self-repairing effect can be achieved by controlling the temperature, thereby improving the self-repairing properties of the anti-aging and anti-corrosion material.

[0023] Secondly, N-(2-(N,N-dimethylamino)ethyl)maleimide reacts with chlorine on the pre-modified layered magnesium aluminum hydroxide to form quaternary ammonium, which has a good antibacterial effect as a cation and can improve the antibacterial properties of the anti-aging and anti-corrosion coating; the modified layered magnesium aluminum hydroxide as a layered structure dispersed in the coating can form a maze effect, extend the diffusion path of oxygen and water molecules to the metal surface, and improve the corrosion resistance of the anti-aging and anti-corrosion coating. The modified layered magnesium aluminum hydroxide will release water and carbon dioxide when heated, which can dilute the combustible gas. Magnesium aluminum hydroxide can also act as a physical barrier to isolate flames and absorb smoke particles, thereby effectively improving the flame retardant properties of the anti-aging and anti-corrosion coating; the modified layered magnesium aluminum hydroxide is obtained by intercalating 3,5-di-tert-butyl-4-hydroxybenzoic acid into the layered magnesium aluminum hydroxide by an ion exchange method. 3,5-di-tert-butyl-4-hydroxybenzoic acid, as an antioxidant, can capture free radicals, thereby achieving an anti-aging effect and improving the anti-aging properties of the anti-aging and anti-corrosion coating. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Embodiment 1:

[0026] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0027] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.3:1.4:75, stirred at room temperature at 400 r / min for 5 h, and the solvent was evaporated at 80° C. The solid product was dissolved in deionized water at 55° C., cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated twice. The filter residue was vacuum dried at 75° C. for 8 h to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0028] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.4:5 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.7:8 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 600 r / min. After the addition is completed, the mixture is allowed to stand for 10 hours, and the precipitate is separated by centrifugation. The precipitate is washed three times with deionized water, and vacuum dried at 75°C for 8 hours to obtain layered magnesium aluminum hydroxide. The layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:4, and ultrasonic treatment was performed for 25 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.3:20, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 400r / min at room temperature for 22h, filtered, and the filter residue was washed with deionized water for 3 times, and vacuum dried at 75°C for 8h to obtain an anti-aging layered magnesium aluminum hydroxide;

[0029] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:8:30, refluxing at 105°C for 22 hours under a nitrogen atmosphere, cooling to room temperature, filtering, washing the filter residue with anhydrous toluene three times, and vacuum drying at 85°C for 4 hours to obtain a pre-modified layered magnesium aluminum hydroxide;

[0030] (4) pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:1.2:8, stirred at 75°C and 600 r / min for 22 hours, filtered, and the filter residue was washed with anhydrous toluene for 3 times, and vacuum dried at 85°C for 4 hours to obtain modified layered magnesium aluminum hydroxide;

[0031] (5) 1 molar portion of polytetrahydrofuran, 0.2 molar portions of 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and 0.2 molar portions of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.2 molar portions of diisobutyltin dilaurate and 20 molar portions of N,N-dimethylformamide are added; 2.8 molar portions of isophorone diisocyanate and 1.2 molar portions of diphenylmethane diisocyanate are mixed and added, and the mixture is stirred at 65° C. and 200 r / min for 2 h to obtain a prepolymer solution;

[0032] (6) The modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:30:0.7, and polyetheramine with a molar number of 1.6 times that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:18 and added, and stirred at 400 r / min at 45° C. for 8 minutes to obtain an anti-aging and anti-corrosion coating.

[0033] Embodiment 2:

[0034] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0035] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.4:1.5:80, stirred at room temperature at 500 r / min for 6 hours, and the solvent was evaporated at 85°C. The solid product was dissolved in deionized water at 60°C, cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated 3 times. The filter residue was vacuum dried at 80°C for 10 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0036] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.5:10 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:10 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 700 r / min. After the addition is completed, the mixture is allowed to stand for 12 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 4 times, and vacuum dried at 80° C. for 10 hours to obtain layered magnesium aluminum hydroxide. Oxide; layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:5, and ultrasonic treatment was performed for 30 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.4:25, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 500r / min at room temperature for 24 hours, filtered, and the filter residue was washed with deionized water for 4 times, and vacuum dried at 80°C for 10 hours to obtain an anti-aging layered magnesium aluminum hydroxide;

[0037] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:10:35, refluxed at 110° C. for 24 h under a nitrogen atmosphere, cooled to room temperature, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90° C. for 5 h to obtain a pre-modified layered magnesium aluminum hydroxide;

[0038] (4) pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:1.3:10, stirred at 80°C and 700 r / min for 24 hours, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90°C for 5 hours to obtain modified layered magnesium aluminum hydroxide;

[0039] (5) 1 molar portion of polytetrahydrofuran, 0.2 molar portions of 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and 0.2 molar portions of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.3 molar portions of diisobutyltin dilaurate and 25 molar portions of N,N-dimethylformamide are added; 2.8 molar portions of isophorone diisocyanate and 1.2 molar portions of diphenylmethane diisocyanate are mixed and added, and the mixture is stirred at 70° C. and 300 r / min for 3 h to obtain a prepolymer solution;

[0040] (6) The modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:35:0.8, and polyetheramine with a molar number of 1.8 times that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:20 and added, and stirred at 500 r / min for 10 min at 50° C. to obtain an anti-aging and anti-corrosion coating.

[0041] Embodiment 3:

[0042] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0043] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.5:1.6:85, stirred at room temperature at 600 r / min for 7 hours, and the solvent was evaporated at 90°C. The solid product was dissolved in deionized water at 65°C, cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated 4 times. The filter residue was vacuum dried at 85°C for 12 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0044] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.6:15 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.9:12 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 800 r / min. After the addition is completed, the mixture is allowed to stand for 14 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 5 times, and vacuum dried at 85° C. for 12 hours to obtain layered magnesium aluminum hydroxide. Oxide; layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:6, and ultrasonic treatment was performed for 35 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.5:30, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 600r / min at room temperature for 26 hours, filtered, and the filter residue was washed with deionized water for 5 times, and vacuum dried at 85°C for 12 hours to obtain an anti-aging layered magnesium aluminum hydroxide;

[0045] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:12:40, refluxing at a constant temperature of 115° C. for 26 hours under a nitrogen atmosphere, cooling to room temperature, filtering, washing the filter residue with anhydrous toluene for 5 times, and vacuum drying at 95° C. for 6 hours to obtain a pre-modified layered magnesium aluminum hydroxide;

[0046] (4) pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:1.4:12, stirred at 85°C and 800 r / min for 26 hours, filtered, and the filter residue was washed with anhydrous toluene for 5 times, and vacuum dried at 95°C for 6 hours to obtain modified layered magnesium aluminum hydroxide;

[0047] (5) 1 molar portion of polytetrahydrofuran, 0.2 molar portions of 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and 0.2 molar portions of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.4 molar portions of diisobutyltin dilaurate and 30 molar portions of N,N-dimethylformamide are added; 2.8 molar portions of isophorone diisocyanate and 1.2 molar portions of diphenylmethane diisocyanate are mixed and added, and the mixture is stirred at 75° C. and 400 r / min for 4 h to obtain a prepolymer solution;

[0048] (6) The modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:40:0.9, and polyetheramine with a molar number twice that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:22 and added, and stirred at 55° C. and 600 r / min for 12 minutes to obtain an anti-aging and anti-corrosion coating.

[0049] Comparative Example 1:

[0050] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0051] (1) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.5:10 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:10 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 700 r / min. After the addition is completed, the mixture is allowed to stand for 12 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 4 times, and vacuum dried at 80° C. for 10 hours to obtain layered magnesium aluminum hydroxide. Oxide; layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:5, and ultrasonic treatment was performed for 30 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.4:25, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 500r / min at room temperature for 24 hours, filtered, and the filter residue was washed with deionized water for 4 times, and vacuum dried at 80°C for 10 hours to obtain an anti-aging layered magnesium aluminum hydroxide;

[0052] (2) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:10:35, refluxed at 110° C. for 24 h under a nitrogen atmosphere, cooled to room temperature, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90° C. for 5 h to obtain a pre-modified layered magnesium aluminum hydroxide;

[0053] (3) pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:1.3:10, stirred at 80°C and 700 r / min for 24 hours, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90°C for 5 hours to obtain modified layered magnesium aluminum hydroxide;

[0054] (4) 1.2 parts by mole of polytetrahydrofuran and 0.2 parts by mole of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.3 times the mass of polytetrahydrofuran diisobutyltin dilaurate and 25 times the mass of polytetrahydrofuran N,N-dimethylformamide are added; 2.8 parts by mole of isophorone diisocyanate and 1.2 parts by mole of diphenylmethane diisocyanate are mixed and added, and stirred at 70° C. and 300 r / min for 3 h to obtain a prepolymer solution;

[0055] (5) The modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:35:0.8, and polyetheramine with a molar number of 1.8 times that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:20 and added, and stirred at 500 r / min for 10 min at 50° C. to obtain an anti-aging and anti-corrosion coating.

[0056] Comparative Example 2:

[0057] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0058] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.4:1.5:80, stirred at room temperature at 500 r / min for 6 hours, and the solvent was evaporated at 85°C. The solid product was dissolved in deionized water at 60°C, cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated 3 times. The filter residue was vacuum dried at 80°C for 10 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0059] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.5:10 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:10 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 700 r / min. After the addition is completed, the mixture is allowed to stand for 12 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 4 times, and vacuum dried at 80° C. for 10 hours to obtain layered magnesium aluminum hydroxide. Oxide; layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:5, and ultrasonic treatment was performed for 30 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.4:25, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 500r / min at room temperature for 24 hours, filtered, and the filter residue was washed with deionized water for 4 times, and vacuum dried at 80°C for 10 hours to obtain an anti-aging layered magnesium aluminum hydroxide;

[0060] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:10:35, refluxed at 110° C. for 24 h under a nitrogen atmosphere, cooled to room temperature, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90° C. for 5 h to obtain a pre-modified layered magnesium aluminum hydroxide;

[0061] (4) pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol were mixed in a mass ratio of 1:1.3:10, stirred at 80°C and 700 r / min for 24 hours, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90°C for 5 hours to obtain modified layered magnesium aluminum hydroxide;

[0062] (5) 1.2 parts by mole of polytetrahydrofuran and 0.2 parts by mole of 1H-pyrrole-2,5-dicarboxaldehyde dioxime were mixed to obtain a mixed solution, and 0.3 times the mass of polytetrahydrofuran diisobutyltin dilaurate and 25 times the mass of polytetrahydrofuran N,N-dimethylformamide were added; 2.8 parts by mole of isophorone diisocyanate and 1.2 parts by mole of diphenylmethane diisocyanate were mixed and added, and stirred at 70° C. and 300 r / min for 3 h to obtain a prepolymer solution;

[0063] (6) The modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:35:0.8, and polyetheramine with a molar number of 1.8 times that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:20 and added, and stirred at 500 r / min for 10 min at 50° C. to obtain an anti-aging and anti-corrosion coating.

[0064] Comparative Example 3:

[0065] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0066] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.4:1.5:80, stirred at room temperature at 500 r / min for 6 hours, and the solvent was evaporated at 85°C. The solid product was dissolved in deionized water at 60°C, cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated 3 times. The filter residue was vacuum dried at 80°C for 10 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0067] (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1:0.5:10 to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1:0.8:10 to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 700 r / min. After the addition is completed, the mixture is allowed to stand for 12 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 4 times, and vacuum dried at 80° C. for 10 hours to obtain layered magnesium aluminum hydroxide. Oxide; layered magnesium aluminum hydroxide and deionized water were mixed at a mass ratio of 1:5, and ultrasonic treatment was performed for 30 minutes to obtain a layered magnesium aluminum hydroxide slurry; 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.4:25, added to the layered magnesium aluminum hydroxide slurry, sealed, stirred at 500r / min at room temperature for 24 hours, filtered, and the filter residue was washed with deionized water for 4 times, and vacuum dried at 80°C for 10 hours to obtain an anti-aging layered magnesium aluminum hydroxide;

[0068] (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1:10:35, refluxed at 110° C. for 24 h under a nitrogen atmosphere, cooled to room temperature, filtered, and the filter residue was washed with anhydrous toluene for 4 times, and vacuum dried at 90° C. for 5 h to obtain a pre-modified layered magnesium aluminum hydroxide;

[0069] (4) 1 molar portion of polytetrahydrofuran, 0.2 molar portions of 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and 0.2 molar portions of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.3 molar portions of diisobutyltin dilaurate and 25 molar portions of N,N-dimethylformamide are added; 2.8 molar portions of isophorone diisocyanate and 1.2 molar portions of diphenylmethane diisocyanate are mixed and added, and the mixture is stirred at 70° C. and 300 r / min for 3 h to obtain a prepolymer solution;

[0070] (5) The pre-modified layered magnesium aluminum hydroxide, the prepolymer solution, and aluminum trichloride were mixed at a mass ratio of 1:35:0.8, and polyether amine with a molar number of 1.8 times that of isophorone isocyanate and N,N-dimethylformamide were mixed at a mass ratio of 1:20 and added, and stirred at 500 r / min for 10 min at 50° C. to obtain an anti-aging and anti-corrosion coating.

[0071] Comparative Example 4:

[0072] A method for preparing an anti-aging and anti-corrosion coating comprises the following preparation steps:

[0073] (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution were mixed in a mass ratio of 1:1.4:1.5:80, stirred at room temperature at 500 r / min for 6 hours, and the solvent was evaporated at 85°C. The solid product was dissolved in deionized water at 60°C, cooled to room temperature, filtered, and the dissolution-cooling-filtration operation was repeated 3 times. The filter residue was vacuum dried at 80°C for 10 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime;

[0074] (2) 1 molar portion of polytetrahydrofuran, 0.2 molar portions of 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and 0.2 molar portions of n-dodecylphosphonic acid are mixed to obtain a mixed solution, and 0.3 molar portions of diisobutyltin dilaurate and 25 molar portions of N,N-dimethylformamide are added; 2.8 molar portions of isophorone diisocyanate and 1.2 molar portions of diphenylmethane diisocyanate are mixed and added, and the mixture is stirred at 70° C. and 300 r / min for 3 h to obtain a prepolymer solution;

[0075] (3) Polyetheramine with a molar number of 1.8 times that of isophorone isocyanate and N,N-dimethylformamide were mixed in a mass ratio of 1:20 and added, and stirred at 500 r / min for 10 min at 50° C. to prepare an anti-aging and anti-corrosion coating.

[0076] Test Example 1:

[0077] Anti-corrosion performance test method: Use a tinplate with a size of 150mm×70mm×3mm as a sample substrate, stir the raw materials thoroughly and evenly disperse them, use a paint brush to dip the anti-aging coating prepared in each embodiment and comparative example and apply it on one end of the sample substrate, place the adjustable film applicator on one end of the sample plate coating, and slowly push it toward the other side so that the coating is evenly attached to the sample plate substrate, and cure and dry at 110℃ for 4h to obtain a coating sample with a coating thickness of 200μm. Put the dried coating samples in the sample rack of the salt spray test box in sequence (the coating sample is placed at an angle of 15° to the spray port), set the spray chamber temperature of the salt spray test box to (35±2)℃, spray continuously, and the salt spray deposition is 1~2mL / h. The solution used in the salt spray test is a homemade sodium chloride aqueous solution with a mass fraction of 3.5%. Observe the corrosion of the sample after 720h of the experiment. The results are shown in Table 1.

[0078] Antibacterial performance test method: The coating materials obtained from the examples and comparative examples were poured into a polytetrafluoroethylene mold, cured and dried at 110°C for 4 hours to obtain a sample, and the sample was crushed into powders of less than 150 microns. The same mass was taken and the antibacterial rate of the material against Staphylococcus aureus was tested according to the Quine test method. The results are shown in Table 1.

[0079] Table 1

[0080] Corrosion Antibacterial rate Corrosion Antibacterial rate Example 1 No corrosion 99.1% Comparative Example 1 Slight corrosion 99.0% Example 2 No corrosion 99.3% Comparative Example 2 No corrosion 89.7% Example 3 No corrosion 99.1% Comparative Example 3 No corrosion 12.5% Comparative Example 4 Slight corrosion 10.7%

[0081] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good anti-corrosion and antibacterial properties.

[0082] By comparison, the corrosion conditions of Examples 1 to 3 are significantly better than that of Comparative Example 1, indicating that the 1H-pyrrole-2,5-dicarboxaldehyde dioxime introduced into the main chain of the coating makes the main chain contain oxime-amino bonds, and the presence of imine bonds can complex metal ions and improve the corrosion resistance of the coating; the corrosion conditions of Examples 1 to 3 are significantly better than that of Comparative Example 4, indicating that the modified layered magnesium aluminum hydroxide as a layered structure dispersed in the coating can form a maze effect, prolong the diffusion path of oxygen and water molecules to the metal surface, and improve the corrosion resistance of the anti-aging and anti-corrosion coating.

[0083] By comparison, the antibacterial rates of Examples 1 to 3 are significantly greater than those of Comparative Examples 3 and 4, indicating that N-(2-(N,N-dimethylamino)ethyl)maleimide reacts with the chlorine on the pre-modified layered magnesium aluminum hydroxide to form quaternary ammonium, which has a good antibacterial effect as a cation and can improve the antibacterial properties of the anti-aging and anti-corrosion coating.

[0084] The anti-corrosion performance of the anti-aging and anti-corrosion coatings is improved by improving the corrosion resistance and antibacterial properties of the anti-aging and anti-corrosion coatings.

[0085] Test Example 2:

[0086] Flame retardant performance test method: The examples and comparative examples were prepared into standard specimens according to GB / T 2406-93, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 2.

[0087] Table 2

[0088] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.6 Comparative Example 1 30.7 Example 2 32.9 Comparative Example 2 24.5 Example 3 32.8 Comparative Example 3 32.1 Comparative Example 4 26.5

[0089] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good flame retardant properties.

[0090] By comparison, the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 2, indicating that n-dodecylphosphonic acid is introduced into the main chain of the coating, and phosphoric acid will undergo dehydration polymerization to regenerate polymetaphosphoric acid under thermal combustion conditions. Polymetaphosphoric acid can quickly catalyze the dehydration and carbonization of the polyurea material to generate a dense protective carbon layer, isolate oxygen and reduce the thermal decomposition rate of the material, so that the maximum mass loss rate of the polyurea gradually decreases, while reducing the heat generated by the decomposition of the coating, thereby improving the flame retardant properties of the anti-aging and anti-corrosion coating; the limiting oxygen index of Examples 1 to 3 is significantly greater than that of Comparative Example 4, indicating that the modified layered magnesium aluminum hydroxide will release water and carbon dioxide when heated, which can dilute the combustible gas, and the magnesium aluminum hydroxide can also act as a physical barrier to isolate flames and absorb smoke particles, thereby effectively improving the flame retardant properties of the anti-aging and anti-corrosion coating.

[0091] Test Example 3:

[0092] Tensile strength test: Each embodiment and comparative example was poured into a polytetrafluoroethylene mold to obtain a sample with a specification of 20 mm × 4 mm × 1 mm, and the tensile strength was tested. The AGS-100N electronic universal testing machine produced by Shimadzu Corporation of Japan was used to test the tensile strength of the samples repaired under different conditions at 20°C, and the tensile rate was 100 mm / min. The results are shown in Table 3.

[0093] Table 3

[0094] Tensile Strength Tensile Strength Example 1 27.68MPa Comparative Example 1 24.72MPa Example 2 28.11MPa Comparative Example 2 27.85MPa Example 3 28.07MPa Comparative Example 3 24.21MPa Comparative Example 4 23.53MPa

[0095] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good tensile strength.

[0096] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 1, 3, and 4, indicating that the pyrrole structure on 1H-pyrrole-2,5-dicarboxaldehyde dioxime undergoes a thermally reversible cross-linking reaction with the maleimide structure on the modified layered magnesium aluminum hydroxide, causing the modified layered magnesium aluminum hydroxide to undergo chemical cross-linking with polyurea, thereby improving the tensile strength of the anti-aging and anti-corrosion coating.

[0097] Test Example 4:

[0098] Self-repair performance test, anti-aging performance test:

[0099] Metal coordination self-repair test: Pour each embodiment and comparative example into a polytetrafluoroethylene mold to obtain a sample with a specification of 20mm×4mm×1mm, obtain an original sample, and test the original tensile strength 1; cut the sample from the middle position, gently put the cut sample together, immerse it in a zinc nitrate solution with a mass concentration of 0.1mol / L for 12h, and then test the tensile strength 1' of the repaired sample after taking it out. The repair efficiency is calculated according to the repair efficiency 1=tensile strength 1' / tensile strength 1. The results are shown in Table 4.

[0100] Thermal reversible self-repair test: Each embodiment and comparative example was poured into a polytetrafluoroethylene mold to obtain a sample with a specification of 20 mm × 4 mm × 1 mm, and the original sample was obtained to test the original tensile strength 2; the sample was cut from the middle position, and the cut sample was gently put together, heated to 110 ° C for 10 minutes, and then cooled to room temperature to test the tensile strength 2' of the repaired sample. The repair efficiency was calculated according to the repair efficiency 2 = tensile strength 2' / tensile strength 2. The results are shown in Table 4.

[0101] Test method 3: Pour each embodiment and comparative example into a polytetrafluoroethylene mold to obtain a sample with a specification of 20mm×4mm×1mm, obtain an original sample, and test the original tensile strength 3; use a xenon lamp to simulate sunlight, put the sample into a xenon lamp accelerated aging test box, the aging time is 360h, the experimental atmosphere is air, the temperature is 65℃, the light source is 25cm away from the sample, and the radiation intensity is 550W / m 2 , the tensile strength 3' was tested again, and the performance decline rate was calculated as 1-tensile strength 3' / tensile strength 3. The results are shown in Table 4.

[0102] The tensile strength of the samples repaired under different conditions was tested at 20°C using an AGS-100N electronic universal testing machine produced by Shimadzu Corporation of Japan, with a tensile rate of 100 mm / min.

[0103] Table 4

[0104]

[0105]

[0106] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the anti-aging and anti-corrosion coating prepared by the present invention has good self-repairing performance and anti-aging performance.

[0107] By comparison, the repair efficiency 1 of Examples 1 to 3 is significantly greater than the repair efficiency 1 of Comparative Example 1, indicating that the introduction of oxime-amino bonds by 1H-pyrrole-2,5-dicarboxaldehyde dioxime on polyurea can complex metal ions to form a cross-linked network, thereby improving the self-repairing performance of the anti-aging and anti-corrosion coating; the repair efficiency 2 of Examples 1 to 3 is significantly greater than the repair efficiency 2 of Comparative Examples 1, 3, and 4, indicating that 1H-pyrrole-2,5-dicarboxaldehyde dioxime introduces a pyrrole structure on polyurea, and undergoes a thermally reversible cross-linking reaction with the maleimide structure on the modified layered magnesium aluminum hydroxide, and the self-repairing effect is achieved by controlling the temperature according to the thermally reversible cross-linking reaction, thereby improving the self-repairing performance of the anti-aging and anti-corrosion material.

[0108] By comparison, the performance degradation rates of Examples 1 to 3 are significantly lower than that of Comparative Example 4, indicating that 3,5-di-tert-butyl-4-hydroxybenzoic acid is intercalated into the layered magnesium aluminum hydroxide by the ion exchange method, and 3,5-di-tert-butyl-4-hydroxybenzoic acid, as an antioxidant, can capture free radicals, thereby achieving an anti-aging effect and improving the anti-aging performance of the anti-aging and anti-corrosion coating.

[0109] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An anti-aging and anti-corrosion coating, characterized in that: The anti-aging and anti-corrosion coating is prepared by mixing a prepolymer solution with modified layered magnesium aluminum hydroxide and polyether amine; The prepolymer solution is prepared by reacting polytetrahydrofuran, 1H-pyrrole-2,5-dicarboxaldehyde dioxime, n-dodecylphosphonic acid with isophorone diisocyanate and diphenylmethane diisocyanate; The modified layered magnesium aluminum hydroxide is prepared by first reacting magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and sodium dodecyl sulfate and then exchanging ions with 3,5-di-tert-butyl-4-hydroxybenzoic acid to obtain the anti-aging layered magnesium aluminum hydroxide; the anti-aging layered magnesium aluminum hydroxide is modified by chloropropyltrimethoxysilane and then reacting with N-(2-(N,N-dimethylamino)ethyl)maleimide to obtain the modified layered magnesium aluminum hydroxide.

2. A method for preparing an anti-aging and anti-corrosion coating, characterized in that: The method comprises the following preparation steps: (1) 1H-pyrrole-2,5-dicarboxaldehyde, hydroxylamine hydrochloride, potassium carbonate and 75% ethanol solution by volume concentration are mixed in a mass ratio of 1: (1.3-1.5): (1.4-1.6): (75-85), stirred at room temperature at 400-600 r / min for 5-7 hours, evaporated to remove the solvent at 80-90° C., dissolved the solid product in deionized water at 55-65° C., cooled to room temperature, filtered, and the dissolution-cooling-filtration operation is repeated 2-4 times, and the filter residue is vacuum dried at 75-85° C. for 8-12 hours to obtain 1H-pyrrole-2,5-dicarboxaldehyde dioxime; (2) Magnesium nitrate hexahydrate, aluminum nitrate nonahydrate, and deionized water are mixed in a mass ratio of 1: (0.4-0.6): (5-15) to obtain a salt solution; sodium hydroxide, sodium dodecyl sulfate, and deionized water are mixed in a mass ratio of 1: (0.7-0.9): (8-12) to obtain an alkaline solution; the salt solution and the alkaline solution are simultaneously added dropwise to a flask at room temperature using a syringe pump, and stirred at 600-800 r / min. After the addition is completed, the mixture is allowed to stand for 10-14 hours, and the precipitate is separated by centrifugation. The precipitate is washed with deionized water for 3-5 times, and vacuum dried at 75-85° C. for 8-12 hours to obtain a layered magnesium aluminum precipitate. Hydroxide; mixing layered magnesium aluminum hydroxide and deionized water in a mass ratio of 1: (4-6), ultrasonically treating for 25-35 minutes to obtain layered magnesium aluminum hydroxide slurry; mixing 3,5-di-tert-butyl-4-hydroxybenzoic acid, sodium hydroxide and deionized water in a mass ratio of 1: (0.3-0.5): (20-30), adding to the layered magnesium aluminum hydroxide slurry, sealing, stirring at 400-600 r / min at room temperature for 22-26 hours, filtering, washing the filter residue with deionized water for 3-5 times, and vacuum drying at 75-85° C. for 8-12 hours to obtain anti-aging layered magnesium aluminum hydroxide; (3) mixing anti-aging layered magnesium aluminum hydroxide, chloropropyltrimethoxysilane, and anhydrous toluene in a mass ratio of 1: (8-12): (30-40), reflux at a constant temperature of 105-115° C. for 22-26 hours under a nitrogen atmosphere, cool to room temperature, filter, wash the filter residue with anhydrous toluene for 3-5 times, and vacuum dry at 85-95° C. for 4-6 hours to obtain a pre-modified layered magnesium aluminum hydroxide; (4) mixing the pre-modified layered magnesium aluminum hydroxide, N-(2-(N,N-dimethylamino)ethyl)maleimide and anhydrous ethanol in a mass ratio of 1:(1.2-1.4):(8-12), stirring at 75-85° C. and 600-800 r / min for 22-26 h, filtering, washing the filter residue with anhydrous toluene for 3-5 times, and vacuum drying at 85-95° C. for 4-6 h to obtain a modified layered magnesium aluminum hydroxide; (5) Polytetrahydrofuran, 1H-pyrrole-2,5-dicarboxaldehyde dioxime, and n-dodecylphosphonic acid are mixed to obtain a mixed solution, and diisobutyltin dilaurate in an amount of 0.2 to 0.4 times the mass of polytetrahydrofuran and N,N-dimethylformamide in an amount of 20 to 30 times the mass of polytetrahydrofuran are added; isophorone diisocyanate and diphenylmethane diisocyanate are mixed in proportion and added, and stirred at 65 to 75° C. and 200 to 400 r / min for 2 to 4 hours to obtain a prepolymer solution; (6) Modified layered magnesium aluminum hydroxide, prepolymer solution, and aluminum trichloride are mixed in a mass ratio of 1: (30-40): (0.7-0.9) are mixed, polyether amine with a molar number of 1.6-2 times of isophorone isocyanate and N,N-dimethylformamide are mixed in a mass ratio of 1: (18-22) and then added, and stirred at 400-600r / min for 8-12min at 45-55°C to obtain an anti-aging and anti-corrosion coating.

3. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The 1H-pyrrole-2,5-dicarboxaldehyde dioxime reaction process described in step (1) is as follows:

4. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The polytetrahydrofuran described in step (5) is polytetrahydrofuran with an average molecular weight of 1000.

5. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The molar ratio of polytetrahydrofuran, 1H-pyrrole-2,5-dicarbaldehyde dioxime, n-dodecylphosphonic acid, isophorone diisocyanate and diphenylmethane diisocyanate in the prepolymer solution of step (5) is 1:0.2:0.2:2.8:1.

2.

6. The method for preparing an anti-aging and anti-corrosion coating according to claim 2, characterized in that: The polyetheramine described in step (7) is T403 type polyetheramine.

Citation Information

Cited By

  • Protective coating for limiting rope in aviation oxygen supply mask pipeline and preparation method of protective coating

    CN120005464A